A dream reflecting the desire to avoid substance use: a case study on unconscious selfprevention effort - Danışman, Mustafa; Zengin İspir, Gamze; Sezer Katar, Kübra (Journal of Dependence, 2025)
Drug-Related Dreams (DRD) are dreams observed in individuals with substance use disorders during withdrawal or recovery periods, containing various substance-related themes. It is known that DRD may include themes such as searching for drugs, attempting to use them, seeing substances but not using or being unable to use them, rejecting an offer to use substances, or witnessing someone else using them. It is thought that when DRD are satisfying in terms of content and emotions (Type A, drug-use dreams), they can help alleviate and manage cravings, leading to a positive prognosis. On the other hand, if these dreams are not satisfying (Type B, failed drug-use attempts), they are believed to reignite and intensify the craving for substances. Instead of assuming that DRD with different content and emotions provide varying levels of satisfaction, analyzing these dreams through the lens of the censorship mechanism may reveal that they aim to satisfy distinct desires. In this paper, the dream and clinical course of a patient who experienced a drug-related dream during inpatient treatment at our clinic, was discharged voluntarily, and later relapsed into substance use, are discussed. When the patient reapplied for inpatient treatment after resuming substance use and was found carrying drugs, their admission could not be processed. The case is examined through the censorship mechanism in dreams. Although the patient was aware of our clinical rules, we interpreted their behavior of seeking admission to our clinic while under the influence of substances not as forgetfulness or an attempt to smuggle substances, but as an unconscious cry for help to overcome their desire to use substances.
Keywords: Cencorship; drug related dreams; substance use